Recognition of signals with different correlation matrixes with quantum logic - Melnichenko, Gregory (Lietuvos matematikos rinkinys, 2005)
It is shown that the quantum logic can be used for recognition of random signals with different correlation operators. Rules of recognition use energy of the accepted signal.
Keywords: quantum logic; recognition of random signals; maximizing the energy of correct recognition; projection; quantum detection